A guide to investigation and indictment using an integrated approach to law enforcement - Santoso, T.; Chandra, R.; Sinaga, A.C.; Muhajir, M.; Mardiah, S. (Center for International Forestry Research, 2011)
Significantly increased rates of deforestation in Indonesia from the 1970s to the 2000s have brought pressure on law enforcement agencies to better enforce the law and prosecute forest crimes. Generally, criminal wrongdoing in the forestry sector is only prosecuted under the provisions of the Forestry Law. Several reports and results of studies suggest that these sanctions are ineffective in stopping crimes in the forestry sector because they only catch the petty criminals in the field. The main actors who fund and plan large-scale illegal activities persistently evade sanctions. Since Illegal logging is in fact a multidimensional crime, several legal instruments in Indonesia can be used to prosecute the perpetrators, including the Forestry Law, the Anti-Corruption Law, the Anti–Money Laundering Law, the Environmental Law and the Law on Customs. The complexity and extent of the network of perpetrators of illegal logging require that law enforcement apply a more unified, integrated and comprehensive approach. This guideline introduces and describes such an integrated approach. CIFOR conducted research to design effective integrated strategies to address the large-scale issues. The project, the Integrated Law Enforcement Approach (ILEA), encourages an integrated approach and specifically promotes the use of anti-corruption and anti–money laundering instruments to better prosecute forest crime. This book presents insights from the ILEA project to guide law enforcement officers in their efforts to combat crime in the forestry sector.